2013
DOI: 10.4028/www.scientific.net/amm.483.429
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Large-Scale Biogas Project Based on System Dynamics

Abstract: With the application and promotion of large-scale biogas project, economic analysis and evaluation of large-scale biogas project are particularly important. However, the benefits of biogas project embodied in the economic, social, ecological, and many other aspects have dispersion, which leads to production decisions in a gray state and investment in conformity. In this paper, the biogas project in Zhuangda village, Zhaozhou County, Heilongjiang province is taken as an example, the supply and demand of funds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Although many vehicle bio-methane projects are underway, their relatively high operating costs and high energy consumption levels are still a major concern. Previous studies have shown that 10-30% of the total energy consumed in typical biogas processes involve heat production [4][5][6], with current process plants being inefficient at recovering waste heat losses. Therefore, the introduction of new processes or technologies that enable the efficient recycling of waste heat is important for improving the economic and environmental efficiency of biogas processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although many vehicle bio-methane projects are underway, their relatively high operating costs and high energy consumption levels are still a major concern. Previous studies have shown that 10-30% of the total energy consumed in typical biogas processes involve heat production [4][5][6], with current process plants being inefficient at recovering waste heat losses. Therefore, the introduction of new processes or technologies that enable the efficient recycling of waste heat is important for improving the economic and environmental efficiency of biogas processes.…”
Section: Introductionmentioning
confidence: 99%